A rare case of congenital heart disease: anomalous origin of coronary artery from innominate artery with coronary fistula and truncus arteriosus. (18th August 2021) - Li, Wenlei; Li, Jianbin; Chen, Xinxin
Abstract: Anomalous origin of a single coronary artery arising from the innominate artery associated with coronary artery fistula and truncus arteriosus is extremely rare. We found this anomaly in a 16-month-old infant-girl who received Rastelli procedure during the operation. The three defects described above are rarely found together; indeed, such a case as ours may be the first reported in the literature.